Urytalpa chandleri sp. n. (Diptera: Keroplatidae) from Turkey, with a key to the Western Palaearctic species of the genus - Bechev, Dimtar; Koç, Hasan (Zootaxa, 2008)
Urytalpa chandleri sp. n. from southwest Asiatic Turkey is described and illustrated. Platyura maritima Becker is transferred to Urytalpa based on examination of the type specimen. A key to the Western Palaearctic species of Urytalpa is provided.